2018
DOI: 10.1371/journal.pone.0193517
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Response Factors (ARFs) are potential mediators of auxin action in tomato response to biotic and abiotic stress (Solanum lycopersicum)

Abstract: Survival biomass production and crop yield are heavily constrained by a wide range of environmental stresses. Several phytohormones among which abscisic acid (ABA), ethylene and salicylic acid (SA) are known to mediate plant responses to these stresses. By contrast, the role of the plant hormone auxin in stress responses remains so far poorly studied. Auxin controls many aspects of plant growth and development, and Auxin Response Factors play a key role in the transcriptional activation or repression of auxin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 86 publications
5
124
1
1
Order By: Relevance
“…Based on another study, auxin is as an active player in plant defense against pathogens (Navarro et al, 2006). Our findings agreed with Bouzroud et al (2018) and Saidi and Hajibarat (2019) that suggested auxin could be implicated in pathogen infections through ARFs.…”
Section: In Silico Analysis Of Degs Expressionsupporting
confidence: 88%
See 1 more Smart Citation
“…Based on another study, auxin is as an active player in plant defense against pathogens (Navarro et al, 2006). Our findings agreed with Bouzroud et al (2018) and Saidi and Hajibarat (2019) that suggested auxin could be implicated in pathogen infections through ARFs.…”
Section: In Silico Analysis Of Degs Expressionsupporting
confidence: 88%
“…Solyc05g008850.3 was down regulated during all the stage-specific tissues such as hypodermis, outer epidermis, parenchyma, seed, locular tissue, endocarp, leaf, flower, columella, generative cell, radical pericarp, ovary wall, fruit, placenta, pericarp, leaflet, inner pericarp, ovule, callus, pistil, placenta, vascular tissue, roots, floral meristem, sympodial inflorescence meristem, and shoot apex. ARF plays a critical role in the transcriptional activation or repression of auxinresponsive genes or IAA through direct binding to their promoters (Bouzroud et al, 2018). Auxin is implicated in plant developmental processes and response to environmental stresses .…”
Section: In Silico Analysis Of Degs Expressionmentioning
confidence: 99%
“…A downregulated or disturbed auxin pathway may enhance susceptibility, as in the case for Arabidopsis mutants and their defense response to necrotrophic fungi (Llorente et al 2008). Bouzroud et al (2018) describe auxin responsive factors (ARFs) as part of biotic and abiotic stress signaling in Solanum. The role of ethylene as a defense regulator has been well established, primarily due to its function as a signaling molecule in the defense against necrotrophic pathogens in combination with jasmonic acid.…”
Section: Common Response To Both Pathogensmentioning
confidence: 99%
“…In the PCRe, an AuxRE and a GCC_box_AP2_EREBP cis-motif are also conserved in seven Oryza species. HLH, NAC and AP2/EREBP transcription factors have well-documented roles under salinity stress (Zhang and Shi, 2013;Chen et al, 2016), while AuxRE bind Auxin Response Factors (ARFs) which are known to be induced in response to salinity (Qi et al, 2012;Bouzroud et al, 2018). The cladogram derived from the order of predicted cis-elements reveals that Oryza species with AA genomes have a distinct pattern of cis-elements that are distinct from BB, FF and KKLL genome types.…”
Section: Upstream Regions Of Oryza Nhx1 Show a Conserved Order Of Cismentioning
confidence: 99%